The dialogue with the forest: what is the limit of the bioeconomy in the Amazon? (Research, Society and Development, 2022)
An antithesis to the unilateral and triumphalist proposals that are being presented to end deforestation and fires in the Amazon supported by the bioeconomy, plant extractivism, agroforestry systems, the sale of carbon credits and environmental services, among the main ones. There is a need to advance on the scientific and technological frontier and not rely solely on the knowledge of indigenous peoples, quilombolas, riverine and traditional populations. There is a need to create income and employment alternatives for more than 761 thousand small producers who live in the Amazon, representing 83% of the universe of producers in the region, in reducing the technological heterogeneity of productive activities, intensifying livestock, reforestation, planting perennial crops and fish farming.  It is urgent to promote (State, Science and Private Initiative) in an articulated vision of the future, based on management, research and planning. Only in this way will the country be able to take advantage of the Amazon's historic window of opportunity to explore its economic potential in harmony with environmental challenges.